The Influence of Audit Time Budget Pressure on Reduced Audit Quality Behavior - Gaol, Manatap Berliana Lumban (Universitas Syiah Kuala, 2018)
Objective The purpose of this study is to examine the effect of audit time budget pressure on audit quality reduction behavior conducted by auditors in Indonesia.Design/methodology 240 respondents for current study where auditors in Indonesia served as the sample. Multivariate technique was deployed to data analysis using AMOS - structural equation modeling.Results The results of this study indicate that the audit quality reduction behavior occurs inthe audit assignment practices and this is becoming a concern inaudit profession. Research finding statistically highlighted that there is a positive and significant relationship between time budget pressure and audit quality reduction behavior.Keywords Audit Quality, Time budget pressure, Reduce Audit Quality Behavior